Modeling the Satisfaction of Bus Traffic Transfer Service Quality at a High-Speed Railway Station - Xiaoyun Cheng; Yu Cao; Kun Huang; Yuejiao Wang (Journal of Advanced Transportation)
Bus transit is one of the main transfer modes at high-speed railway (HSR) stations. Performing a scientific and reasonable evaluation of the present bus traffic transfer service is highly significant for improving the efficiency of the HSR and increasing the use of the system. This paper focuses on the passengers’ transfer experience and proposes a methodology to evaluate current bus traffic transfer service. Factors that affect passenger satisfaction during the bus transfer process at HSR stations based on the passengers’ perceptions are analyzed by convenience, comfort, safety, service, and economy. A structural equation model (SEM) is developed as an evaluation approach to explore the correlations of bus transfer service, passenger perceived value, and passenger satisfaction. To calibrate the model, a questionnaire survey of passengers transferring to a bus was conducted at Xi’anbei Railway Station. This paper analyzes the relationships between observed variables and latent variables in the measured model, the influences of exogenous variables on endogenous variables in the structural model, and the impact of the passengers’ socioeconomic attributes on passenger satisfaction. Analysis results of the SEM show that economy and convenience are the critical influential indicators of passenger satisfaction, among which bus fare preferential policy and transfer distance are the most significant factors. The findings can provide helpful information for planners and managers to improve the services of existing HSR stations and to guide the planning of new ones.